Peripheral venous congestion causes time‐ and dose‐dependent release of endothelin‐1 in humans. Issue 6 (21st March 2017) - Lin, Jeffrey; Chudasama, Neelesh; Hayashi, Yacki; Hawk, Christopher; Ramnauth, Sahadeo D.; Wong, Ka Yuk; Harxhi, Ante; Onat, Duygu; Wakabayashi, Michiyori; Uriel, Nir; Jorde, Ulrich P.; LeJemtel, Thierry H.; et al.
Abstract: Endothelin‐1 (ET‐1) is a pivotal mediator of vasoconstriction and inflammation in congestive states such as heart failure (HF) and chronic kidney disease (CKD). Whether peripheral venous congestion (VC) increases plasma ET‐1 at pressures commonly seen in HF and CKD patients is unknown. We seek to characterize whether peripheral VC promotes time‐ and dose‐dependent increases in plasma ET‐1 and whether these changes are sustained after decongestion. We used a randomized, cross‐over design in 20 healthy subjects (age 30 ± 7 years). To experimentally model VC, venous pressure was increased to either 15 or 30 mmHg (randomized at first visit) above baseline by inflating a cuff around the subject's dominant arm; the nondominant arm served as a noncongested control. We measured plasma ET‐1 at baseline, after 20, 60 and 120 min of VC, and finally at 180 min (60 min after cuff release and decongestion). Plasma ET‐1 progressively and significantly increased over 120 min in the congested arm relative to the control arm and to baseline values. This effect was dose‐dependent: ET‐1 increased by 45% and 100% at VC doses of 15 and 30 mmHg, respectively ( P < 0.05), and declined after 60 min of decongestion though remaining significantly elevated compared to baseline. In summary, peripheral VC causes time‐ and dose‐dependent increases in plasma ET‐1. Of note, the lower dose of 15 mmHg (more clinically relevant to HF and CKD patients) was sufficient to raise ET‐1. These findings support the potentially contributory, not merely consequential, role of VC in the pathophysiology of HF and CKD. Abstract : Peripheral venous congestion is an important consequence of disease states such as heart failure and chronic kidney disease, but may also be a causal factor. This study highlights the potential novel role of venous congestion in an in vivo human model in mediating vasoconstriction and inflammation through the release of endothelin‐1.